A novel monolithic controlled delivery system of resveratrol for enhanced hepatoprotection: nanoformulation development, pharmacokinetics and pharmacodynamics. (1st September 2016) - Singh, Anjali; Ahmad, Iqbal; Ahmad, Sayeed; Iqbal, Zeenat; Ahmad, Farhan J.
Abstract: The current investigation aims to present a novel solid lipid-based nanoparticulate system of resveratrol (RV) for the effective treatment of liver cirrhosis. A simplified solvent injection method was employed and the Box–Behnken experimental design was applied for optimization to get a window particle size of 150–200 nm having maximum entrapment efficiency as well as % release. Optimized resveratrol solid lipid nanoparticles (RV-SLNs) (SR-1) of appropriate characteristics (particle size = 191.1 ± 10.44 nm; zeta potential= −13.56 ± 4.14 mV; entrapment efficiency = 75.23 ± 3.85%; maximum % release = 80.53 ± 3.99%) were produced. Differential scanning calorimetry and X-ray diffraction studies were carried out which collectively proved the reduced crystallinity and stability enhancing the effect of the SLNs. Improved drug stability was further established by the appreciable shelf-life of the formulation from International Council for Harmonisation of Technical Requirements for Pharmaceuticals for Human Use (ICH)-recommended accelerated stability studies. In vivo studies revealed nearly five-fold increase in the bioavailability of SR-1 (AUC0→∞ =3411 ± 170.34 µg/ml/h) as compared to RV suspension (AUC0→∞ =653.5 ± 30.10 µg/ml/h). Pharmacodynamic data exhibited a significant decrease in the serum biomarker enzymes (serum glutamic oxalo-acetic transaminase (SGOT), serum glutamic pyruvic transaminase (SGPT) and alkaline phosphatase) after oral administration of RV-SLNs as compared to control and marketed (SILYBON ® ) formulations against paracetamol-induced liver cirrhosis. The effect of the treatment was confirmed by the histopathology of the liver microtome sections. Finally, reverse transcriptase-polymerase chain reaction studies were conducted on isolated liver mRNA from SR-1 treated animals and significant down-regulation of tissue inhibitor of metalloproteinases-1 and nuclear factor-kB was witnessed.